Genetic associations for two biological age measures point to distinct aging phenotypes. Issue 6 (26th May 2021) - Kuo, Chia‐Ling; Pilling, Luke C.; Liu, Zuyun; Atkins, Janice L.; Levine, Morgan E.
Abstract: Biological age measures outperform chronological age in predicting various aging outcomes, yet little is known regarding genetic predisposition. We performed genome‐wide association scans of two age‐adjusted biological age measures (PhenoAgeAcceleration and BioAgeAcceleration), estimated from clinical biochemistry markers (Levine et al., 2018; Levine, 2013) in European‐descent participants from UK Biobank. The strongest signals were found in the APOE gene, tagged by the two major protein‐coding SNPs, PhenoAgeAccel—rs429358 ( APOE e4 determinant) ( p  = 1.50 × 10 −72 ); BioAgeAccel—rs7412 ( APOE e2 determinant) ( p  = 3.16 × 10 −60 ). Interestingly, we observed inverse APOE e2 and e4 associations and unique pathway enrichments when comparing the two biological age measures. Genes associated with BioAgeAccel were enriched in lipid related pathways, while genes associated with PhenoAgeAccel showed enrichment for immune system, cell function, and carbohydrate homeostasis pathways, suggesting the two measures capture different aging domains. Our study reaffirms that aging patterns are heterogeneous across individuals, and the manner in which a person ages may be partly attributed to genetic predisposition. Abstract : A genome‐wide association study for differences in aging rates was performed in the UK Biobank sample using two previously established aging measures. Results suggest that one was associated with genes involved in lipid metabolism and blood pressure, while the other was associated with genes involved in immune functioning. APOE e4 was associated with faster aging in the measure reflecting lipid age, yet paradoxically, was associated with reduced aging in the measure reflecting immune functioning and inflammation.